Post harvest bacterial load in the gut of Ompok pabda (Hamilton, 1822) from two fish markets of Brahmanbaria (Bangladesh Journal of Zoology, 2019)
This study was conducted to enumerate the post harvest bacterial load in the gut of captured and cultured Ompok pabda by spread plate method using different selective culture media. The bateriological parameters, such as total viable bacterial counts (TVBC), total coliform counts (TCC), total fecal coliform counts (E. coli), pathogenic bacteria Salmonella spp, Shigella spp. and Vibrio cholerae were determined. Highest bacterial load was found in the month of July and lowest in January. The quantitative and qualitative aspects of gut microbes showed that TVBC of captured O. pabda were found 9.2 × 106, 7.0 × 107, 9.5 × 106 cfu/g and that of cultured fish were 1.56 × 107, 7.2 × 107 and 2.24 × 107 cfu/g during pre-monsoon, monsooon and post-monsoon, respectively. The bacteriological quality of fish from both captured and cultured sources did not comply with ICMSF standard. Pathogenic bacteria E. coli, Salmonella spp., Shigella spp. and Vibrio cholerae were also detected from both captured and cultured O. pabda. The findings of this study indicated that the fish collected from the local fish markets were contaminated with different pathogenic bacteria that reflect the unhygienic conditions of the markets.Bangladesh J. Zool. 47(2): 243-251, 2019